Reconstruction of the Handling of Non-Performing Financing in Murabahah Contracts in Islamic Banking - Khairul Hanif; Muhammad Albahi; Raja Sakti Putra Harahap (LP2M IAIN Palopo, 2026)
This study aims to analyze the issues surrounding the management of non-performing financing in murabahah contracts within Islamic banking and to formulate a revised management model that is more in line with Sharia principles and legal certainty. This issue is significant given the widespread use of murabahah contracts in Islamic banking practices, which is not always accompanied by the substantive implementation of Sharia principles. The research method employed is a normative legal approach using a literature review, through an examination of primary legal sources relevant to Islamic banking and murabahah financing. Data analysis was conducted qualitatively using descriptive-analytical and prescriptive approaches to produce comprehensive model recommendations. The results indicate that the handling of non-performing financing in murabahah contracts still faces a gap between theory and practice, a dominance of repressive approaches, and weak legal certainty due to the lack of alignment between regulations and on-the-ground implementation. To address this, this study proposes a reconstruction of the management of non-performing financing through a model based on legal certainty and Sharia principles, consisting of three stages: preventive, curative, and repressive, with consultation and restructuring as the primary approaches and enforcement as the last resort (ultimum remedium). It is hoped that the implications of this study will contribute to the development of Islamic banking law, particularly in creating a system for handling non-performing financing that is fairer, more effective, and in accordance with Sharia principles, as well as serving as a reference for practitioners, regulators, and academics in strengthening the implementation of Islamic banking in Indonesia.